INVESTIGAÇÃO DE MODY 3 EM PACIENTES DO AMBULATÓRIO DE DM 1 DO HOSPITAL UNIVERSITÁRIO DA UNIVERSIDADE FEDERAL DO MARANHÃO (HUUFMA) - Almeida, Ana Gregória Ferreira Pereira de (2012)
Maturity onset diabetes of young 3 (MODY 3) is the most common monogenic autosomal dominant diabetes caused by mutations in the HNF 1A and characterized by a defect in insulin secretion, decreased renal threshold for glucose and sensitivity to sulfonureia. It is often misdiagnosed as DM 1 or DM 2. By this evidence, this study aims to investigate the HNF 1A gene mutations in patients treated at the outpatient clinic of the University Hospital of DM1 UFMA Sao Luis - MA (HUUFMA), characterize epidemiologically the study population, and identify and describe the mutations found in the gene, correlating them with the chronic complications of diabetes that these patients may have. We evaluated by questionnaire 60 patients with a previous diagnosis of DM 1. These, 20 patients were selected for their clinical features suggestive of MODY for molecular analysis of the HNF 1A gene by sequencing technique. Eleven patients were females and nine males with a mean age of 24.35 ± 6.91 years. Twenty five per cent had retinopathy, 55 %, nephropathy, neuropathy 35 % and 15 % ischemic heart disease. Among the gene variations were found 53 mutations, of these, a deletion in the promoter. Of the 52 variations that occurred in exons, 15 were silent. Among the non- silent, there were 29 missense mutations, seven deletions and one nonsense. Of these, 11 mutations were found in the A isoform, two in the AB isoform and 24 in the ABC isoform. Regarding the fields of protein, it was found: one missense mutation in the dimerization domain, nine mutations in the DNA-binding domain and 25 mutations in the transactivation domain. By correlating the types of mutations, their locations in their respective gene or protein domains with typical chronic complications of diabetes, there was no relationship. However, it was observed that patients with frameshift mutations associated with missense mutations in the transactivation domain had a worse metabolic control than patients with missense mutations in the same domain. With these results we conclude that changes in gene HNF 1A are very common among diabetic patients with a typical characteristics of MODY in this sample, suggesting that the MODY 3 can be cause of DM in many of these patients and the type of mutation and its location in the field protein may be associated with metabolic control in these patients.